Standard dose and low-dose rituximab combined with glucocorticoids and cyclophosphamide in the treatment of acquired haemophilia A - Cai, Mingxia; Guo, Xizhe; Zhang, Xueya (Frontiers in Immunology, 2025)
AimTo investigate the efficacy and safety of standard dose and low-dose rituximab combined with corticosteroids and cyclophosphamide in the treatment of acquired haemophilia A.MethodsA retrospective analysis was conducted on the clinical manifestations, laboratory tests, diagnosis and treatment process, and efficacy of 11 patients with acquired haemophilia A.ResultsAmong the 11 patients, there were 6 males and 5 females with median age 64 years old (29-88 years); 11 patients had no underlying diseases before onset. Clinical manifestations include varying degrees of skin bruising, with 1 case accompanied by muscle hematoma, 1 case accompanied by gastrointestinal bleeding, and 1 case accompanied by abdominal hematoma; The laboratory examination showed an APTT prolongation of 85.97 ± 27.26 seconds, which could not be corrected after incubation with normal plasma for 2 hours; FVIII: C activity 0.93 ± 1.51%; The titer of FVIII inhibitor is 15.19 ± 14.32BU; All 11 patients received a combination of prothrombin complex and fresh frozen plasma for hemostasis, with 1 patient receiving a single platelet transfusion; Among the 11 patients, 7 received a standard dose of rituximab (375mg/m2/w × 1w) combined with corticosteroids and cyclophosphamide regimen, and 4 received a low-dose rituximab (100mg/w × 4w) combined with corticosteroids and cyclophosphamide regimen. The APTT recovery time was 37.3 ± 8.6 days, 43.6 ± 11.4 days (P>0.05), and the FVIII activity increased to normal time was 30.2 ± 9.8 days, 40.2 ± 18.8 days (P<0.05), respectively; The time for FVIII inhibitor to turn negative was 56.3 ± 23.5 days and 63.9 ± 29.1 days, respectively (P<0.05); Four weeks after treatment, there was no statistically significant difference in the levels of B lymphocyte antigen, IgG, IgA, IgM, and incidence of adverse reactions between the two groups (P>0.05).ConclusionsAcquired haemophilia A is rare in clinical practice, with severe and common bleeding manifestations. Fresh frozen plasma combined with prothrombin complex had a good hemostatic effect. The standard dose of rituximab combined with corticosteroids and cyclophosphamide can quickly increase FVIII activity and eradicate FVIII inhibitors compared to the low dose of rituximab regimen, although there is no difference in efficacy and safefy between the two treatment regimens.